ESTIMATION OF GEOMORPHOLOGICAL RESOURCES OF NORTHERN ARMENIA FOR DEVELOPMENT OF RECREATION AND TOURISM (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The article presents an assessment of geomorphological resources in the areas of recreation and the development of tourism. The study was carried out on the steepness and exposure of slopes. Based on the results, a large-scale map of the angles of inclination and exposures of the territory of Northern Armenia was compiled.
Keywords: Northern Armenia; morphometry; relief; recreation; resource; map; assessment; cartography; tourism; geography